Supportive service workers and their impact on children in UAE society - Almaazmi, Mashail; Alsadi, Asma (Al-Adab Journal, 2025)
The text explains assisted employment provides important support to UAE families, but requires conscious supervision to ensure that family values and healthy upbringing of children are protected. It refers to the effects of social and economic changes, such as the shift from extended families to nuclear families and increased reliance on household chores. The text raises the question of the impact of domestic service on children, as such employment goes beyond its traditional role and has a negative impact on children's social and cultural upbringing.The study aimed to identify the categories of service workers, the pros and cons of their use, and their impact on children's social and cultural upbringing. The study used the analytical descriptive curriculum and the results showed that domestic labour was a category of workers under Federal Decree No. 9 of 2022. Research has also found that it has many benefits, especially for working women and obtaining a place in society, relying on domestic workers may help the UAE family manage its affairs, but it requires awareness and controls to reduce its negative impact on children and ensure a balanced upbringing in keeping with the UAE's inherent values. The study recommends the need to establish legal controls on the use of domestic labour and to raise parents' awareness of the importance of their role in education.